Population structure-guided profiling of antibiotic resistance patterns in clinical Listeria monocytogenes isolates from Germany identifies pbpB3 alleles associated with low levels of cephalosporin resistance. Issue 1 (1st January 2020) - Fischer, Martin A.; Wamp, Sabrina; Fruth, Angelika; Allerberger, Franz; Flieger, Antje; Halbedel, Sven
ABSTRACT: Numbers of listeriosis illnesses have been increasing in Germany and the European Union during the last decade. In addition, reports on the occurrence of antibiotic resistance in Listeria monocytogenes in clinical and environmental isolates are accumulating. The susceptibility towards 14 antibiotics was tested in a selection of clinical L. monocytogenes isolates to get a more precise picture of the development and manifestation of antibiotic resistance in the L. monocytogenes population. Based on the population structure determined by core genome multi locus sequence typing (cgMLST) 544 out of 1220 sequenced strains collected in Germany between 2009 and 2019 were selected to cover the phylogenetic diversity observed in the clinical L. monocytogenes population. All isolates tested were susceptible towards ampicillin, penicillin and co-trimoxazole – the most relevant antibiotics in the treatment of listeriosis. Resistance to daptomycin and ciprofloxacin was observed in 493 (91%) and in 71 (13%) of 544 isolates, respectively. While all tested strains showed resistance towards ceftriaxone, their resistance levels varied widely between 4 mg/L and >128 mg/L. An allelic variation of the penicillin binding protein gene pbpB3 was identified as the cause of this difference in ceftriaxone resistance levels. This study is the first population structure-guided analysis of antimicrobial resistance in recent clinical isolates and confirms the importance of penicillin binding protein B3 (PBP B3) for the high level of intrinsic cephalosporin resistance of L. monocytogenes on a population-wide scale.